2003
DOI: 10.1191/0960327103pm779oa
|View full text |Cite
|
Sign up to set email alerts
|

The impact on the family of terminal restlessness and its management

Abstract: The purpose of this qualitative study was to explore and describe the impact of terminal restlessness and its management upon family members who were witness to the event. Approximately 25%-85% of terminally ill patients may experience the symptoms associated with terminal restlessness during the hours or days before their death. They may be physically agitated and cognitively impaired and often appear to be suffering. Treatment of these severe symptoms usually involves the use of sedating medications that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(101 citation statements)
references
References 39 publications
2
93
0
4
Order By: Relevance
“…Considering that Epoch 1 data indicated a mean MMSE of 1.7, it is possible that some of these residents were near death 18 months later. Various researchers have found that an increase in agitation occurs near death and may actually be a marker for near death (Allen, Burgio, Fisher, Hardin, & Shuster, 2005;Brajtman, 2003;Jones, King, Speck, Kurowsaka, & Tookman, 1998). Unfortunately, in this study we do not have data on when residents died.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that Epoch 1 data indicated a mean MMSE of 1.7, it is possible that some of these residents were near death 18 months later. Various researchers have found that an increase in agitation occurs near death and may actually be a marker for near death (Allen, Burgio, Fisher, Hardin, & Shuster, 2005;Brajtman, 2003;Jones, King, Speck, Kurowsaka, & Tookman, 1998). Unfortunately, in this study we do not have data on when residents died.…”
Section: Discussionmentioning
confidence: 99%
“…HLM has the capacity to analyze information about the rate and the pattern of change in targeted variables over multiple time points, taking into account inter-and intraindividual variability in change and cross-level interactions of time with predictors (Raudenbush & Bryk, 2002;Singer, 1998;Snijders & Bosker, 1999). We conducted HLM analyses separately for staff ratings and direct observation of agitation using the PROC MIXED procedure in SAS for Windows 9.1 (SAS Institute, 2002/2003. We examined main effects (i.e., factors that predict variability in baseline agitation) and cross-level interactions (i.e., interaction between predictors and time effect).…”
Section: Analysesmentioning
confidence: 99%
“…Delirium increases distress for family members (11,12), especially at the end of life where communication is impaired (73,74,78). In M A N U S C R I P T…”
Section: Pharmacological Intervention With a More Sedating Approach Omentioning
confidence: 99%
“…8 In the last days or hours of life, hyperactive delirium symptoms-commonly referred to as "terminal agitation" or "terminal restlessness"-cause distress for family members. [9][10][11] Core symptoms for a Diagnostic and Statistical Manual (DSM), Fourth Edition (DSM-IV) diagnosis of delirium include disturbed consciousness, with reduced ability to focus, sustain, or shift attention; altered cognition or a perceptual disturbance, acute onset and fluctuating symptoms, which can be mild and fleeting or severe and persistent; and evidence of an etiological cause. 12 Level of consciousness identifies the three delirium subtypes: hyperactive, hypoactive, or mixed.…”
Section: Introductionmentioning
confidence: 99%